Characteristics of traumatic brain injury patients with abnormal neuroimaging in Southeast Norway - Cathrine Tverdal; Mads Aarhus; Nada Andelic; Ola Skaansar; Karoline Skogen; Eirik Helseth (BMC, 2020)
Abstract Background The vast majority of hospital admitted patients with traumatic brain injury (TBI) will have intracranial injury identified by neuroimaging, requiring qualified staff and hospital beds. Moreover, increased pressure in health care services is expected because of an aging population. Thus, a regular evaluation of characteristics of hospital admitted patients with TBI is needed. Oslo TBI Registry - Neurosurgery prospectively register all patients with TBI identified by neuroimaging admitted to a trauma center for southeast part of Norway. The purpose of this study is to describe this patient population with respect to case load, time of admission, age, comorbidity, injury mechanism, injury characteristics, length of stay, and 30-days survival. Methods Data for 5 years was extracted from Oslo TBI Registry - Neurosurgery. Case load, time of admission, age, sex, comorbidity, injury mechanism, injury characteristics, length of stay, and 30-days survival was compiled and compared. Results From January 1st, 2015 to December 31st, 2019, 2153 consecutive patients with TBI identified by neuroimaging were registered. The admission rate of TBI of all severities has been stable year-round since 2015. Mean age was 52 years (standard deviation 25, range 0-99), and 68% were males. Comorbidities were common; 28% with pre-injury ASA score of ≥3 and 25% used antithrombotic medication. The dominating cause of injury in all ages was falls (55%) but increased with age. Upon admission, the head injury was classified as mild TBI in 46%, moderate in 28%, and severe (Glasgow coma score ≤ 8) in 26%. Case load was stable without seasonal variation. Majority of patients (68%) were admitted during evening, night or weekend. 68% was admitted to intensive care unit. Length of hospital stay was 4 days (median, interquartile range 3-9). 30-day survival for mild, moderate and severe TBI was 98, 94 and 69%, respectively. Conclusions The typical TBI patients admitted to hospital with abnormal neuroimaging were aged 50-79 years, often with significant comorbidity, and admitted outside ordinary working hours. This suggests the necessity for all-hour presence of competent health care professionals.